Stromal Neutrophil Extracellular Trap Density Is an Independent Prognostic Factor for Cervical Cancer Recurrence - Yan, Bin; Dai, Xuan; Ma, Quanfu; Wu, Xufeng (Frontiers in Oncology, 2021)
Background Emerging evidence indicates that the tumor microenvironment influences tumor progression and patient prognosis through various inflammatory cells. Polymorphonuclear neutrophils (PMNs) and their functional structures termed neutrophil extracellular traps (NETs) are prominent constituents of several malignant tumors and affect the tumor microenvironment and cancer evolution. Here, we investigate the prognostic value of PMNs and NETs for recurrence in patients with cervical cancer. Methods The study comprised 126 cervical cancer patients who were retrospectively enrolled. CD66b+ neutrophils and myeloperoxidase/citrullinated histone H3 (MPO/H3Cit)-labeled NETs were assessed by immunofluorescence, and the relationships with clinical and histopathologic features and patient outcome were evaluated. Results The highest density of CD66b+ neutrophils were observed in the stromal compartment (median 55 cells/mm2). Above median densities of stromal CD66b+ neutrophils and NETs were significantly associated with short recurrence-free survival (RFS) (P = 0.041 and P = 0.006, respectively). Multivariate analysis identified high clinical stage (hazard ratio [HR] 6.40; 95% confidence interval [CI] 3.51-11.64; P < 0.001), lymph node metastases (HR 4.69; 95% CI 3.09-9.66; P = 0.006) and high density of NETs (HR 2.66; 95% CI 1.21-5.82; P = 0.015) as independent prognostic factors for short RFS, whereas a high density of CD66b+ neutrophils was not significant. Patients with a high NET density showed worse recurrence status in every stage, but the difference was only significant for stage I (P = 0.042), not stages II, III, or IV (all P > 0.05). Combining stromal NET density and the tumor, nodes, metastasis (TNM) staging system had better prognostic accuracy for cervical cancer than the TNM staging system alone at five and six years respectively (P = 0.010 and P = 0.023). Conclusion Stromal NET density is an independent prognostic factor for RFS in cervical cancer. Combining NETs with the TNM staging system may further improve prognostic stratification.